Local support among arctic residents to a land tenure reform in Finnmark, Norway - Broderstad, Else Grete; Hausner, Vera Helene; Josefsen, Eva; Søreng, Siri Ulfsdatter (Land Use Policy, 2019)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Claims for indigenous rights to land and resources are influencing land use policies worldwide. The public’s support for such land tenure arrangements has rarely been investigated. We present a unique case from the Norwegian Arctic, where land claims made by the indigenous Sami people have resulted in the transfer of land tenure and resource management from the government to the residents of Finnmark in 2005. Based on indigenous land claims, a management agency was established, the Finnmark Estate (FeFo), which on the operational level provides Sami and non-Sami users the same services. Public debates and conflicts among politicians and the public framed the political process leading up to this establishment. Based on a survey and interviews in Finnmark, we explored the public’s support for the new land tenure arrangements. We use the term diffuse support to investigate whether residents conform to FeFo’s basic ideas, values and principles, while specific support refers to the supportive attitudes for management actions carried out by the institution. We conclude that there is a general low diffuse support for FeFo among the residents in Finnmark, but a relatively high specific support for the policies and management actions implemented by the estate among those who have experiences with FeFo. We explain the gap between diffuse- and specific support by the historical, social and political processes which led up to the establishment of the land tenure arrangements.